2023
DOI: 10.1186/s13098-022-00975-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of intrinsic capacity and obesity on the KDIGO chronic kidney disease risk classification in older patients with type 2 diabetes mellitus

Abstract: Background Intrinsic capacity (IC) is a novel concept focusing on normal and healthy aging. The effect of IC on the risk of chronic kidney disease (CKD) according to KDIGO category in older type 2 diabetes mellitus (T2DM) patients has rarely been studied. We investigated whether a decline in IC is associated with the risk of CKD according to KDIGO 2012 categories. Methods This is a cross-sectional study. The exposure variables (IC score and body ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Only one study (Lin et al., 2022) showed that older adults with worse IC were less likely to be smokers than those with better IC. However, no association was found in the other two studies (Jia et al., 2023; Tang et al., 2023).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Only one study (Lin et al., 2022) showed that older adults with worse IC were less likely to be smokers than those with better IC. However, no association was found in the other two studies (Jia et al., 2023; Tang et al., 2023).…”
Section: Resultsmentioning
confidence: 83%
“…19 of the 29 studies looked at the effect of age on the IC of older adults, involving 95,732 participants. Eighteen studies (Beard et al., 2019; Beard et al., 2022; Campbell et al., 2022; Jia et al., 2023; Leung et al., 2022; Lin et al., 2022; Lu et al., 2021; Ma et al., 2021a; Muneera et al., 2022; Prince et al., 2021; Tang et al., 2023; Wu et al., 2022; Yu et al., 2021; Yu et al., 2022a; Yu et al., 2022b; Yu et al., 2022c; Yu et al., 2023; Zhao et al., 2021) discovered a significant association between age and IC of older adults, indicating that the younger old adults were likely to have a better IC. And only one study (Ma et al., 2021c) showed no differences between age and IC of older adults.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations